2006
DOI: 10.1007/s00405-006-0031-0
|View full text |Cite
|
Sign up to set email alerts
|

Modified endoscopic swallowing test for improved diagnosis and prevention of aspiration

Abstract: Laryngopharyngeal sensation is important in the normal process of swallowing, it is often impaired after neurological events and it has been common practice in such an occurrence to order non-oral tube feeding to prevent aspiration. This study assesses a novel approach to the evaluation of the laryngopharyngeal sensation that allows for improved triage of aspiration risk and more lenience towards oral feeding. This is a case series with follow-up period ranging from 6 to 24 months. Forty patients with neurolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 14 publications
0
7
0
3
Order By: Relevance
“…FEES has been shown to be safe and effective for assisting in swallowing evaluation, and in therapy as a visual display to help patients learn various swallowing manoeuvres. [ 4 , 10 – 13 ]. It can be used in a wide variety of settings, ranging from office evaluation of swallowing, inpatient and outpatient services to critically ill patient treated at the ICU [ 14 – 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…FEES has been shown to be safe and effective for assisting in swallowing evaluation, and in therapy as a visual display to help patients learn various swallowing manoeuvres. [ 4 , 10 – 13 ]. It can be used in a wide variety of settings, ranging from office evaluation of swallowing, inpatient and outpatient services to critically ill patient treated at the ICU [ 14 – 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various non-noxious stimuli, including mechanical, taste and thermal stimuli, may be involved in natural swallowing. Many researchers have reported that impaired laryngeal mechanosensation is associated with the occurrence of aspiration of food boluses and aspiration pneumonia in patients with dysphagia (Kidd et al 1993;Aviv et al 1997;Flaksman et al 2006;Onofri et al 2014). Setzen et al (2003) reported that severe pharyngolaryngeal sensory deficits were associated with aspiration of thin liquids regardless of the integrity of pharyngeal motor function.…”
Section: Introductionmentioning
confidence: 99%
“…Our results are consistent with those from several clinical investigations that also indicate that FEES is effective for swallowing evaluation. 5 , 12 However, FEES still remains an invasive procedure. We showed that a clinical examination assessing the pharyngeal phase with swallowing can be used as an initial test when FEES and videofluoroscopy are not available in detecting postextubation swallowing disorders.…”
Section: Methodsmentioning
confidence: 99%
“…FEES allows visualization of the pharyngeal phase of swallowing and may be performed easily at the bedside but depends on the availability of an experienced endoscopist. 5 , 12 …”
Section: Methodsmentioning
confidence: 99%